Relationship between expectations and satisfaction on technical knowledge - an empathic attitude in the clinical practice of nursing students. Hospital de emergencias Grau EsSalud, 2019.: Relación entre expectativas y satisfacción sobre el conocimiento técnico - actitud empática en las practicas clínica de estudiantes de enfermería. Hospital de emergencias Grau EsSalud, 2019. - Miguel Sinchez, Sonia E. (2021)
Objective: To determine the relationship between expectations and satisfaction regarding technical knowledge - empathic attitude in the clinical practices of nursing students at the Grau de EsSalud Emergency Hospital in 2019. Methods: A study with a quantitative approach, observational type, and correlational design showed 80 nursing students who carried out their clinical practices at the Hospital de Emergencias Grau participated in 2019. Results: Nursing students were characterized by an average age of 21.36 years, 75% were female, and 72.5% were single. The expectations and satisfaction regarding technical knowledge - empathic attitude in the clinical practices of nursing students were high levels in 97.5% and medium level in 60%, respectively. There was no significant relationship between expectations and satisfaction regarding technical knowledge - the empathic attitude of the clinical practices of nursing students (p = 0.661). Conclusion: There is no relationship between expectations and satisfaction regarding technical knowledge - empathic attitude in the clinical practices of nursing students at Hospital de Emergencias Grau de EsSalud in 2019.